Unexpected Geographic Variability of the Free Running Period in the Linden Bug Pyrrhocoris apterus - Pivarciova, Lenka; Vaneckova, Hanka; Provaznik, Jan; Wu, Bulah Chia-Hsiang; Pivarci, Martin; Peckova, Olga; Bazalova, Olga; Cada, Stepan; Kment, Petr; Kotwica-Rolinska, Joanna; Dolezel, David (Journal of biological rhythms, 2016)
Circadian clocks keep organisms in synchrony with external day-night cycles. The free running period (FRP) of the clock, however, is usually only close to-not exactly-24 h. Here, we explored the geographical variation in the FRP of the linden bug, Pyrrhocoris apterus, in 59 field-lines originating from a wide variety of localities representing geographically different environments. We have identified a remarkable range in the FRPs between field-lines, with the fastest clock at ~21 h and the slowest close to 28 h, a range comparable to the collections of clock mutants in model organisms. Similarly, field-lines differed in the percentage of rhythmic individuals, with a minimum of 13.8% and a maximum of 86.8%. Although the FRP correlates with the latitude and perhaps with the altitude of the locality, the actual function of this FRP diversity is currently unclear. With the recent technological progress of massive parallel sequencing and genome editing, we can expect remarkable progress in elucidating the genetic basis of similar geographic variants in P. apterus or in similar emerging model species of chronobiology.
Keywords: Europe, Eastern; Pyrrhocoris apterus; pohybová aktivita; phylogeography; zeměpis; cirkadiánní rytmus; circadian clock; východní Evropa; Phylogeny; population rhythm; altitude; locomotor activity; latitude; Geography; Female; diapause; Tilia; zvířata; Europe; period gene; časové faktory; Izrael; Circadian Rhythm; Circadian Clocks; ženské pohlaví; Male; fylogeneze; geographic distribution; Heteroptera; cirkadiánní hodiny; Motor Activity; Animals; mužské pohlaví; Israel; Time Factors; Evropa